Optimalisasi Presentasi Pada Pembelajaran Daring Dengan Fitur Multimedia Microsoft Power Point - Wardhana, Ariyani; Irvan, Muhamad (ADI MASSI (JURNAL PENGABDIAN MASYARAKAT SISTEM INFORMASI), 2021)
The COVID-19 pandemic has affected the teaching and learning process, where online transitions are a must at every level of education. This creates anxiety for teachers who are not familiar with online learning in preparing teaching materials that can be easily understood and attractive to their students, especially for Reform Vocational Schools that are affected by the large-scale social restriction (PSBB) policy. The teachers hope to maximize presentations in online learning by using the multimedia features available in Microsoft Power Point in order to provide clearer illustrations and facilitate mastery of material for Reformed Vocational High School students. The addition of pictures, videos, and audio in the presentation will provide enrichment of material that is easier for students to understand. This community service activity is carried out via gmeet. Due to the limited interaction that can be carried out between instructors and participants using webinars, less material is delivered but focuses on achieving results. Kata Kunci: Microsoft power point, webinars, image editing, templates, videos, multimedia